The Effect of 5S and Kaizen on Productivity through Work Safety at DSV Solutions Indonesia Bekasi in 2024 - Guti Syahanawa; Rafie Fadhilah; Rohana Sitanggang; Tiarto Tiarto (Jurnal Siber Multi Disiplin, 2026)
Implementation of 5S (Sort,Set in Order,Shine,Standardize,Sustain) and Kaizen can improve work safety and productivity. In improving DSV Solutions Indonesia productivity, necessary to implement 5S and Kaizen. Objective of this research is to examine the impact of 5S and Kaizen Implementation on Productivity directly and also wants to analyze how the role of The role of Work Safety as an intermediary in the indirect correlation between 5S and Kaizen on Productivity at DSV Solutions Indonesia. This research uses a quantitative approach, with the type of explanatory survey research and the sampling technique used is purposive sampling with the Slovin formula. The population consists of 884 employees with a sample of 90 respondents. Data were collected through observation and Likert scale-based questionnaires, the data was examined with Structural Equation Modeling PLS (SEM-PLS). The research findings proved that the application of 5s and kaizen had significant effects on work safety and productivity.